Open innovation in the ICT industry: Substantiation from Poland - Józef Ober (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Open innovation (OI) is among the key strategic resources of enterprises, especially in high-tech sectors such as the ICT industry. The use of OI platforms and/or networks that facilitate access to and sharing of OI knowledge is gaining increasing interest. This study aimed to assess the factors motivating and hindering the use of OI platforms and/or networks in the ICT industry in Poland. The uniqueness of this approach lies in the use of a PROFIT analysis to develop proprietary models of the importance of the various motivating factors and barriers to the use of OI platforms and/or networks in the ICT industry in relation to the job position held. This study hypothesized that the knowledge of factors motivating and hindering the use of OI platforms and/or networks in the ICT industry varies across occupational groups. In order to verify the hypothesis and answer the formulated research questions, a diagnostic survey method with a survey technique was used. The results of this study confirm that the job position occupied by employees in the ICT industry is relevant to each of the factors that pose obstacles to their use of OI platforms and/or networks. Managers and management, as well as developers, are less likely to restrict the use of the aforementioned solutions due to organizational and/or administrative barriers, while more likely due to reluctance to share knowledge. For specialists and analysts, legal barriers and NIH syndrome are greater obstacles. For programmers, negative attitudes toward open innovation and lack of internal commitment to the company are less of an obstacle. Insufficient support from top management is a major barrier for administrative staff and programmers. The conclusions formulated can be useful in practice for managers in the ICT industry to make optimal use of access to OI.
Keywords: 650; innovativeness; open innovation; ICT; innovations; networks; platforms; Poland